Drugs, Society & human behavior - Hart, Carl l. (McGraw-Hill, 2011)
Drugs, Society and Human Behavior provides the latest information on drug use and its effects on society as well as on the individual. Trusted for more than 30 years by both instructors and students, this authoritative resource examines drugs and drug use from a variety of perspectives―behavioral, pharmacological, historical, social, legal, and clinical.